Context-Aware Android Applications Testing - Almeida, Diego Rodrigues de; Machado, Patrícia D. L.; Andrade, Wilkerson L. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Context-aware applications (CAAs) are those that use information from the environment based on sensors such as gyroscope, GPS, and accelerometer. Compared to desktop and web applications, there are additional challenges to test CAAs. It is necessary to take input from users and sensors into account, which can lead to the explosion of possible situations. This work aims to present an approach that makes it possible to automate the black-box testing of context-aware Android applications that follow paths using GPS. Our approach consists of selecting, through pairwise testing, combinations of sensor values with events that occur during the execution of the application under test (AUT). The approach is implemented in a tool supporting GPS-based applications. The approach and tool were analyzed through an empirical study with four real GPS-based applications. Initial results show they can be effective in detecting possible defects related to the context.